Grounding and comparing ecological habitus in environmental communities - Jeff Kirby (International Journal of Urban Sustainable Development, 2018)
In this article, I relate the theoretical concept of ecological habitus to the specific context of environmental communities in the UK. I begin by summarizing sociological literature relating to ecological habitus and then draw upon a qualitative study of four environmental communities to ground the concept. The themes of economy, architecture, leisure, food and water are employed to capture daily communal activities that contribute to a specific form of habitus, namely ecological habitus. Theoretical frameworks within the social field are also examined. Differences relating to environmental philosophy held by community members (reformist environmentalism and ecologism) are seen to direct habitus and attitudes relating to natural and built habitats. Two variants of ecological habitus are consequently identified and judged worthy of further categorization, namely ecological habitus and reformist ecological habitus.